A Review on Rabbit Hemorrhagic Disease with a Special Reference to Egyptian Situation - ABD EL-GHANY, WAFAA A (Journal of the Hellenic Veterinary Medical Society, 2020)
Rabbit hemorrhagic disease (RHD) is considered as one of the most important viral diseases that affects and threatens rabbit’s flocks. This disease has affected rabbits since mid-1980. Two epidemics of RHD had been discovered; the first was in mid-1980 and known as classical RHD virus (RHDV), while the second was in 2011 and described as variant virus (RHDVb/RHDV2). Domestic and wild rabbits are susceptible to RHD. All ages can be affected, but adults are more susceptible to young kitten. RHD is presented in three forms; per-acute, acute and subacute or chronic form. Mortality rate is usually high especially in per-acute and acute stages and it is associated with disseminated intravascular coagulopathy and necrotic hepatitis. The main lesions have been observed in the liver, lungs and spleen. Diagnosis of RHD is based on the clinical picture and detection of RHDV or specific antibodies. The prevention and control strategies depend mainly on using of preventive inactivated vaccine together with adoptionof hygienic measures. However, there is no specific treatment of RHDV infection. So, this review article puts a spot light on RHD regarding the epidemiology, the clinical and laboratory diagnosis as well as the prevention and control strategies with a special reference to Egyptian situation.